2022
DOI: 10.1038/s41598-022-08819-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities associated with silage of different forage crops in Malaysian climate analysed using 16S amplicon metagenomics

Abstract: Silage produced in tropical countries is prone to spoilage because of high humidity and temperature. Therefore, determining indigenous bacteria as potential inoculants is important to improve silage quality. This study aimed to determine bacterial community and functional changes associated with ensiling using amplicon metagenomics and to predict potential bacterial additives associated with silage quality in the Malaysian climate. Silages of two forage crops (sweet corn and Napier) were prepared, and their fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Compared with the CK treatment, PL and LPL treatments upregulated the metabolism of membrane transport, carbohydrate, lipid, and terpenoids and polyketides. This might be due to the fact that the addition of LAB enhanced the utilization of available carbohydrates to produce lactic acid, acetic acid, and terpenoids and polyketides, which transported these fermentation substrates and end-products intracellular or extracellular for bacterial cell division ( Kanehisa, 2019 ; Hisham et al, 2022 ). Herein, the relative abundance of amino acid metabolism was higher in the additive-treated silages than the CK silage, which was inconsistent with the finding of Bai et al (2022) , who reported that amino acid metabolism was predicted to be downregulated in well-preserved silages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the CK treatment, PL and LPL treatments upregulated the metabolism of membrane transport, carbohydrate, lipid, and terpenoids and polyketides. This might be due to the fact that the addition of LAB enhanced the utilization of available carbohydrates to produce lactic acid, acetic acid, and terpenoids and polyketides, which transported these fermentation substrates and end-products intracellular or extracellular for bacterial cell division ( Kanehisa, 2019 ; Hisham et al, 2022 ). Herein, the relative abundance of amino acid metabolism was higher in the additive-treated silages than the CK silage, which was inconsistent with the finding of Bai et al (2022) , who reported that amino acid metabolism was predicted to be downregulated in well-preserved silages.…”
Section: Discussionmentioning
confidence: 99%
“…These decreased genetic functions in the additive-treated silages were probably due to lower pH inhibiting the undesirable microorganisms, and reflected a more stable bacterial community in these silages. Furthermore, the increased metabolism of terpenoids and polyketides in the additive-treated silages might indicate an increase in the synthesis of terpenoids and polyketides that are related to promotion of antimicrobial activities for inhibiting pathogen ( Hisham et al, 2022 ). Promotion of antimicrobial activity against pathogens would be supported by downregulated infectious diseases metabolism with the additives compared with the CK.…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have focused on the effects of chemical or LAB inoculants on fermentation quality and aerobic stability; few have focused on microbial communities in corn silage under tropical climate conditions using NGS or SMRT. Hisham et al ( 2022 ) reported that Pseudomonas , Leuconostoc , and Weissella were the major epiphytic bacteria of sweet corn silage, with Lactobacilli becoming the dominant genus after ensiling.…”
Section: Lactic Acid Bacteria Modulating Microbial Community Structur...mentioning
confidence: 99%
“…Acinetobacter , Pseudomonas , Lactococcus , Mrakiella , and Hannaella were the dominant bacteria in Napier grass cultivated in Chongqing, China, while Lactobacilli , Sphingomonas , and Methylobacterium were the predominant bacteria in Napier grass cultivated in Guangzhou, China (Wang, Li, et al, 2022 ). In addition, Weissella and Pantoea were the dominant genera in Napier grass in Malaysia (Hisham et al, 2022 ). Interestingly, Weissella and Lactobacilli were the dominant genera in Napier grass silages from different regions, and LAB inoculants or wilting treatments regulated the structure of microbial communities (Hisham et al, 2022 ; Yin et al, 2021 ; Zi et al, 2021 ).…”
Section: Lactic Acid Bacteria Modulating Microbial Community Structur...mentioning
confidence: 99%
See 1 more Smart Citation